The Physical Treatment Soil Characteristics for Grounding Systems on Madiun and Surabaya Region - Anggoro, Bambang; Sinisuka, Ngapuli I.; Pakpahan, Parouli M.; B., Dicky Irman (IPTEK The Journal for Technology and Science, 2025)
The research on soil characteristic by measuring soil resistancy and resistivity is an important factor to make a good grounding impedance. The optimal evaluation and planning of the grounding system can be achieved by understanding the soil structure and characteristic. The soil resistivity varies upon soil composition, temperature, water content and its chemical content. In this research we analyse soil characteristics of the samples from Madiun and Surabaya areas by conducting some physical treatments such as water, salt, and carbon treatments. These samples then are tested using 0Hz – 15MHz frequency from sinusoidal power supply. Generally, soil impedance has a negative correlation upon addition of water and salt content, but has no correlation upon additional carbon content.